A research methodology in the service of critical thinking: Hermeneutic approach in the post-truth era - Arriazu, Rubén (Education Policy Analysis Archives, 2018)
The hermeneutic methodology is an analytical and dialectical approach that is irreplaceable for the development of critical thinking. In the post-truth era, the traditional interpretation of text has given way to more complex interpretative instances in which audiovisual content is the basis of new narratives and new knowledge. Qualitative methodological research has always claimed socio-historical and temporal prominence in the analysis of social phenomena. Accepting this premise, hermeneutics is presented as a plausible methodological research strategy for analyzing the representation of a social fact. Specifically, the aim of this research is to show the potential of hermeneutic analysis by examining two opposing versions of the terrorist attack that took place at the headquarters of the satirical weekly magazine, Charlie Hebdo, in 2015. To conduct this analysis the researcher has used the hermeneutic methodology of suspicion (Gadamer, 1960/2004). A main conclusion is that the Internet has become a catalyst for multiple truths in the post-truth era. The Internet is an exhaust pipeline where critical thinking is expounded. The Internet, in short, is a space of resistance where people are able to question the mainstream media’s versions and interpretations of events as imposed by the elite Davos Class.